2015
DOI: 10.1007/s10867-015-9402-3
|View full text |Cite
|
Sign up to set email alerts
|

High-order nonlinear excitations in the Joyeux-Buyukdagli model of DNA

Abstract: By means of the semidiscrete multiple-scale method, we study the existence and properties of high-order envelope solitons and discrete breathers in a homogeneous DNA chain model that is based on pairing enthalpies and site-dependent finite stacking. We obtain the analytical solutions for an envelope soliton, and find that at the Brillouin zone center, discrete breather solutions can appear below the bottom of the phonon band. The behavior of two solitons in collisions and the stability of discrete breathers ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
(40 reference statements)
0
2
0
Order By: Relevance
“…Here we have paid our attention on the Joyeux and Buyukdagli (JB) model [34] in which the stacking interaction potential is finite in contrary to the Peyrard-Bishop-Dauxois (PBD) model [33] where such interaction potential is infinite. Very recently Yao et al [35] have showed that the JB model supports envelope solitons and discrete breathers that have been demonstrated to be very crucial in the transport and localization energy processes [43,[36][37][38]42]. The Hamiltonian of an homogenous JB model reads:…”
Section: A Dna-neuron Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we have paid our attention on the Joyeux and Buyukdagli (JB) model [34] in which the stacking interaction potential is finite in contrary to the Peyrard-Bishop-Dauxois (PBD) model [33] where such interaction potential is infinite. Very recently Yao et al [35] have showed that the JB model supports envelope solitons and discrete breathers that have been demonstrated to be very crucial in the transport and localization energy processes [43,[36][37][38]42]. The Hamiltonian of an homogenous JB model reads:…”
Section: A Dna-neuron Modelmentioning
confidence: 99%
“…DNA is a thread-like chain of nucleotides carrying the genetic information used in the growth, development, functioning and reproduction of all known living organisms and many viruses. During the last decades, neuronal activity and DNA dynamics [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] have received much interest because of their implications in most biological processes governing the behavior of all living cells, animals and plants.…”
Section: Introductionmentioning
confidence: 99%